2016
DOI: 10.1007/s11239-015-1317-0
|View full text |Cite|
|
Sign up to set email alerts
|

Guidance for the treatment of deep vein thrombosis and pulmonary embolism

Abstract: This guidance document focuses on the diagnosis and treatment of venous thromboembolism (VTE). Efficient, cost effective diagnosis of VTE is facilitated by combining medical history and physical examination with pre-test probability models, D dimer testing and selective use of confirmatory imaging. Clinical prediction rules, biomarkers and imaging can be used to tailor therapy to disease severity. Anticoagulation options for acute VTE include unfractionated heparin, low molecular weight heparin, fondaparinux a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
197
0
18

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(217 citation statements)
references
References 155 publications
2
197
0
18
Order By: Relevance
“…Thrombin is not only a key protein in the cascade of fibrin clot formation but also a potent inducer of platelet aggregation. [17][18][19] Dabigatran is a competitive reversible nonpeptide antagonist of thrombin. Most of the actions of thrombin are inhibited in vitro by dabigatran.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombin is not only a key protein in the cascade of fibrin clot formation but also a potent inducer of platelet aggregation. [17][18][19] Dabigatran is a competitive reversible nonpeptide antagonist of thrombin. Most of the actions of thrombin are inhibited in vitro by dabigatran.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with DVT of the leg or PE who receive extended therapy, no need to change the choice of anticoagulant after the first 3 months (Grade 2C) Phase III studies indicated that dabigatran, rivaroxaban, apixaban or edoxaban ["novel" NOACs/"direct" DOACs/"target-specific" TSOAs -all the names, being "La même Jeannette, mais autrement coiffée"] are a more convenient alternative with practical advantages, as effective as the conventional therapy with LMWH and vitamin K antagonists (warfarin, acenocumarol) for the acute VTE [6][7][8][9][10] and for extended prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…This class of new discovered oral anticoagulants brings consistent efficacy (reduced recurrent VTE or VTE-related death compared to placebo) [11], relative safety (significantly reducing the risks of major bleeding) [6,12] and convenience, compared with antivitamin K (acenocumrol or warfarin) [13].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnoses can be made with a good clinical exam evaluating the Wells score (or assimilated) plus quantification of D-dimers and realization of duplex ultrasound for lower legs DVT and/ or CT angiography for PE [3]. These sites have been widely studied for the presence of hidden or obvious cancers, such as MPNs.…”
Section: Introductionmentioning
confidence: 99%